Homology of labial chaetae in Entomobryoidea (Collembola) - Zhang, Feng; Pan, Zhi-Xiang (Zootaxa, 2020)
The labium in Collembola consists of three parts (Folsom 1899): labial palp, basomedian (submentum) and basolateral (mentum) fields. Labial chaetotaxy, i.e. number, nature and relative position of chaetae, has been one of the standard descriptive components for species diagnoses in Entomobryoidea. Labial palp, including labial papillae, guard chaetae and proximal chaetae, has been well investigated across major collembolan lineages by Fjellberg (1999). For the chaetae behind the labial palp (mentum and submentum, Figs 1‒2) in Entomobryoidea, Gisin (1964) introduced the nomenclature of a1‒a5 for the anterior row and M1M2rEL1L2 for the posterior row in Lepidocyrtus; the lowercase letter r represented a smaller chaeta between M and E. Later, Gisin (1967) applied this system to Pseudosinella but defined uppercase and lowercase letters as ciliate and smooth chaetae, respectively. Chen & Christiansen (1993) mostly followed Gisin’s nomenclature but named the anterior row as A, B, C, D and F. When there was more than one chaeta inner to R, M-series, they were designated as M1, M2, Ms (supplementary) etc. Smooth chaeta r was sometimes named as ‘v’ (vestigial) in Lepidocyrtinae when it was very tiny. Because the degree of plurichaetosis on submentum greatly differs among Entomobryoidea species, homology of basomedian chaetae may be incorrectly recognized in adults. In this study, we observed labial chaetotaxy (guard chaetae of labial palp excluded) of early instars in twenty species, clarified their homologies and unified the nomenclature systems.